Gender-sensitive verses in the Qur'an : an analytical study of Amina Wadud's and Asma Barlas' hermeneutics - Adam, Ibrahim Ilyasu (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This dissertation examines gender-sensitive verses in the Qur'an as reinterpreted by Muslim feminists, placing particular emphasis on Amina Wadud and Asma Barlas. The aim of the dissertation is to analyse to what extent Wadud's and Barlas' perception of gender equality shaped their Qur'anic hermeneutics. Over the last two decades, tafsir has gained a new momentum with the emergence of Muslim feminist hermeneutics, an exegetical method used by feminists to reread the Qur'an to advance gender equality within an Islamic paradigm. This is particularly true for Wadud and Barlas who concisely argue that classical exegetes manipulated tafsir to oppress women and preserve 'male-centric' authority. Hence, contextualization of the Qur'an by adopting a new gender-sensitive approach is necessary to ensure women's active participation in tafsir. Using this approach, Wadud and Barlas propose a new hermeneutics to reread the Qur'an and deconstruct specific verses to discredit what they call patriarchal fallacy. While mainstream tafsir relies heavily on using hadith for the most authentic interpretation, Wadud and Barlas have all but disregard its authority, arguing that hadith-based Qur'anic hermeneutics should end. This dissertation analyses their hermeneutics within an Islamic framework and evaluates the extent to which they break with mainstream tafsÊr. In the course of engagement with both feminists, the study adopts a comparative exegetical approach, (al-Tafsir al-Muqaran) making special reference to some classical exegetes such as al-Tabari, as well as some modern intellectuals who have made substantial contributions to Qur'anic scholarship. Similarly, it comparatively examines the point of similarities and differences between Wadud's and Barlas' hermeneutics. The study has found that Wadud's and Barlas' hermeneutical methodology is flawed for disregarding authentic sources of tafsÊr and deviation from its principles and forcing their own reading in to the Qur'Én to provide theological legitimacy to a gender-orientated discourse, Islamic feminism. It argues that revitalization in tafsÊr is essential in light of modern challenges but it has to be based on sound principles of interpretation. Therefore, the study suggests alternatives ways of addressing the problems of women within an Islamic framework rather than adopting a new hermeneutics for reading the Qur'an